Congenital transmission of Neospora caninum in wild ungulates and foxes - Zanet, Stefania; Poncina, Manuela; Ferroglio, Ezio (Frontiers in Veterinary Science, 2023)
Neospora caninum is one of the main causes of abortion in cattle. In wildlife, the occurrence and relevance of vertical infection have not been yet clearly evaluated. The aim of this study was to verify the possibility of vertical transmission of N. caninum in three wild species extensively distributed in Europe, namely roe deer Capreolus capreolus, wild boar Sus scrofa and red fox Vulpes vulpes. A total of 190 foetuses (72 wild boars, 67 foxes and 51 roe deer) from 61 females were included in the study. All animals, which were either found dead or culled within selective control plans in North-western Italy, were tested, in parallel by PCR on central nervous system, skeletal muscle and kidney. The efficiency of vertical transmission in the three target species was of 87.5% (95% CI 69.00 -95.66). Positivity of the mother to N. caninum PCR was a strong risk factor for the development of the infection in foetuses (2=47.88, p=0.000; OR=11.98; CI95% 5.39 – 28.41%). The gestational stage was positively associated with infection in roe deer and wild boar foetuses. Our results confirm, for the first time, the possibility of N. caninum’s congenital transmission in wild ungulates and carnivores, highlighting the important role of this route in the maintenance of the parasite within a sylvatic cycle.